Analysis of Sheikh AnsÄriâs techniques for the criticism of chain of transmission of hÄ«dith - Ã˜Â¯Ã›ÂŒÃ™Â…Ã™Â‡ ÃšÂ©Ã˜Â§Ã˜Â±, Ã™Â…Ã˜ÂÃ˜Â³Ã™Â†; Ã˜Â¨Ã˜Â§Ã™Â‚Ã˜Â±Ã›ÂŒ, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯ Ã™Â…Ã™Â‡Ã˜Â¯Ã›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Sheikh Murtaza AnsÄrai is regarded as one of the greatest Imamite jurists, and one of the prominent scholarly and juristic figures of the last centuries. His proficiency, originality and gumption are evident in his surviving works regarding problems in principles (usÅ«l) and traditional-demonstrative jurisprudence. His precious researches on âinvestigation and criticism of chain of transmission of hadÄ«thâ, which manifest his skill and innovation in the science dealing with the transmitters (âilm al-rijÄl) as well as principles of criticism of hadith, on the one hand, and the significant function of academic methodology in the present time, on the other hand, necessitates, more than any time before, a rereading of Sheikh AnsÄriâs system of thought regarding traditional jurisprudence in general and the criticism of hadith in particular. The present descriptive analytical study, which is done with a lot of research on Sheikh AnsÄriâs works on jurisprudence and its principles, seeks the introduction of Sheikh AnsÄriâs methodology of systematic thinking concerning âthe techniques of the criticism of chain of transmission of hadithâ in traditional-demonstrative jurisprudence. Our investigations show that the most important techniques Sheikh Ansari applied in his criticism of chain of transmission of hadÄ«th consist of the following items: paying atterntion to the personality characteristics of the transmitters (like the people of consensus (ashab al-ijmaâ), trustworthy sheikhs (mashÄyikh al-thiqa), Ahmad b. âIsÄ narrated from him (rawÄ« âanh), sons of faá¸á¸Äl (banÄ« faá¸á¸Äl)), paying attention to the concealment of the original teller of the hadÄ«th (iá¸mÄr-i hadÄ«th), cohesion of the chain of transmitters (ittiá¹£Äl-i sanad), mentioning the anonymity of the transmitters, paying attention to the sameness of the names of the transmitters, and compensation (injibÄr) for the weakness of hadÄ«th.